PENGARUH SUPERVISI PENGAWAS SEKOLAH DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SMP DI KOTA METRO LAMPUNG - Rubiyah Astuti; M. Ihsan Dacholfany (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2016)
This study aims to analyze: 1) The influence of the regulatory supervision of the school on teacher performance, 2) The influence of school leadership on teacher performance, and 3) the influence of the regulatory supervision and leadership principals together on the performance of teachers, as many as 71 teachers are used as samples are 30 teachers and 30 as a research trial. There is a positive and significant The influence of supervision the supervisor and leadership the principle to teachers performance. The result of this study indicate that better supervision the supervisor and leadership the principle it will be better the contribution to the performance of Junior school teachers Metro City